Breakthrough Candidemia in Pediatric Patients With Cancer From a Brazilian Center. Issue 3 (8th February 2021) - Barrientos, Anna Carlota Mott; Nobrega de Almeida Junior, João; Litvinov, Nadia; Bain, Vera; Cristofani, Lilian Maria; Badue Pereira, Maria Fernanda; Sanson Yoshino de Paula, Camila; Lopes Motta, Adriana; Rossi, Flavia; Bárbaro Del Negro, Gilda Maria; Yamamoto Thomaz, Danilo; Sousa Marques, Heloisa Helena
Abstract : We analyzed 19 cases of breakthrough candidemia from a referral pediatric cancer center in Brazil. All patients had neutropenia and were under antifungal prophylactic regimens, mostly micafungin (68%). Most of the patients were treated with amphotericin B formulations and 30-day mortality was 21%. Candida parapsilosis was the main etiologic agent (63%), and horizontal transmission was not evidenced by microsatellite analysis.